Entrustable professional activities for pharmacy students: A primer for solid organ transplant preceptors. (5th August 2021) - Lichvar, Alicia; Chandran, Mary Moss; Do, Vincent; Rendulic, TrisAnn; Szczepanik, Amanda; Pierce, Dana; Park, Jeong M
Abstract: Purpose: The role of a solid organ transplant pharmacist is multifaceted and translates to diverse experiential and elective learning experiences that can be provided to pharmacy learners. Here we provide a guide to integrating pharmacy students into patient care and other pharmacist activities in solid organ transplantation. Summary: Thoughtful incorporation of learners into clinical practice and clinical research creates a positive learning environment for pharmacy students that can foster the development of core skills necessary for students to become "practice-ready" and "team-ready" pharmacy graduates and can equip them with valuable skills to incorporate into the specialty practice areas and careers they pursue. To help develop educational experiences, attention to the list of core entrustable professional activities (EPAs) established by the American Association of Colleges of Pharmacy can help create a rich environment of learning with carefully cultivated tasks. Furthermore, learners can serve as transplant pharmacist extenders to assist in overall patient care and multidisciplinary involvement on the transplant team. This article serves as a "how-to" guide for applying the EPA framework to integrating pharmacy students in patient care and other pharmacist activities in solid organ transplantation and other specialty practice areas. Conclusion: As pharmacy preceptors design and operationalize their teaching to incorporate EPAs, they can benefit from recommendations tailored to specialty practice areas such as solid organ transplantation. Students may start and finish these experiences at different EPA levels, but continuance of training will allow them to achieve the final EPA level across the 6 EPA domains.